Privacy and data security for grid‐connected home area network using Internet of Things. Issue 6 (1st November 2018) - Manimuthu, Arunmozhi; Ramesh, Ramadoss
Abstract : Sensors with IoT assistance provides secured communication and data integrity inside HAN. Energy reading and information flow from the smart grid, together with sensors, bring about a new perspective on energy management. This paper primarily investigates the secured data flow in HAN and assures data privacy of customers during critical and emergency operations. Data are made available in real time with minimum transit time delay. Devices are continuously monitored for vital and emergency services. This paper focuses on machine to machine data flow and packet delivery using IoT. It helps in making user's power consumption data available over the cloud and also in customised electronic devices in real‐time. This research work showcases the requirements for developing a cost‐effective IoT‐HAN connected with smart grid for energy aware routing. The advanced design scheme helps to place sensors, and control gateway in a well‐defined boundary, consuming less energy for data transfer and data processing. Data flow pattern and packet delivery rate is tested using both simulated and actual data from sensors and concentrators. The obtained results and flow pattern is evaluated using MATLAB and network simulator. The developed IoT‐HAN setup is optimally helpful in secured data exchange among different connected devices inside HAN.